PERAN INTERVENSI APOTEKER DALAM KEPATUHAN MINUM OBAT PASIEN HIPERTENSI: TINJAUAN SISTEMATIS - Akri, Yusnita Julyarni; Puspitasari, Diny (ASSYIFA : Jurnal Ilmu Kesehatan, 2025)
One of the factors that often hinders medication adherence is unwanted side effects or interactions with other medications that are being used. Pharmacists have in-depth knowledge of pharmacology and drug interactions, so they can provide information to patients on how to manage those side effects. This study aims to systematically review the role of pharmacists in medication adherence of hypertensive patients. The literature search will be carried out in March 2025. Systematic reviews are carried out by searching for articles from Google Scholar. Keywords for searching this article include "intervention" or "pharmacist" or "compliance" or "taking medication" or "hypertension". Of the 580 articles collected through an initial search on Google Scholar, the author identified 4 articles regarding the role of pharmacists in medication adherence of hypertensive patients. Adherence to medication in hypertensive patients is essential to control blood pressure and prevent further complications. Pharmacists have a very strategic role in improving patient compliance by providing clear education, monitoring medication use, dealing with side effects, providing motivational support, and collaborating with other health workers.